2021
DOI: 10.18494/sam.2021.3318
|View full text |Cite
|
Sign up to set email alerts
|

Ag Concentration Dependence of Build-up Effect of Radio-photoluminescence in Ag-doped P2O5–Al2O3–Na2O–SiO2 Glasses

Abstract: In this paper, we evaluated the Ag concentration dependence of the build-up effect of radiophotoluminescence (RPL) in Ag-doped P 2 O 5 -Al 2 O 3 -Na 2 O-SiO 2 (PANS) glasses. After X-ray irradiation, the Ag-doped PANS glasses showed two emission peaks at around 460 and 630 nm, assigned to blue and orange RPL components, respectively. The build-up curves of the orange RPL component had two components corresponding to the formation of the + 2 Ag dimer and Ag 2+ ions. The intensity of the component due to the + 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In addition, while personal dose monitoring applications require an effective atomic number (Z eff ) close to that of the human body in terms of bioequivalence (Z eff = 7.29), based on the composition of C 5 H 40 O 18 N, (4) IP applications such as dental diagnostics require a large Z eff for high detection efficiency. Various material forms such as single crystals, (5)(6)(7) ceramics, (8)(9)(10)(11)(12)(13) and glasses (14,15) have been investigated for dosimeter applications, and glasses have industrial advantages such as a low production cost and high moldability in comparison with single crystals and ceramics. (16) However, only Ag-doped phosphate glasses have been commercially applied in practical use, (17,18) and there have been only a few reports on the TSL and OSL properties of glasses with a large Z eff .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, while personal dose monitoring applications require an effective atomic number (Z eff ) close to that of the human body in terms of bioequivalence (Z eff = 7.29), based on the composition of C 5 H 40 O 18 N, (4) IP applications such as dental diagnostics require a large Z eff for high detection efficiency. Various material forms such as single crystals, (5)(6)(7) ceramics, (8)(9)(10)(11)(12)(13) and glasses (14,15) have been investigated for dosimeter applications, and glasses have industrial advantages such as a low production cost and high moldability in comparison with single crystals and ceramics. (16) However, only Ag-doped phosphate glasses have been commercially applied in practical use, (17,18) and there have been only a few reports on the TSL and OSL properties of glasses with a large Z eff .…”
Section: Introductionmentioning
confidence: 99%
“…This glass has been used as glass badges for personal monitoring provided by Chiyoda Technol Corporation. (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) It has been reported that the glass system exhibits radiophotoluminescence (RPL), (21)(22)(23)(24)(25)(26) a luminescence owing to electronic transitions within luminescent centers that are generated in phosphors by ionizing radiation. Radiation-induced effects in solid materials have been reported in a variety of fields.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate scintillation, TSL, and OSL properties, many materials such as single crystals, (14)(15)(16)(17)(18)(19)(20)(21)(22) ceramics, (23)(24)(25)(26)(27)(28)(29) and glasses (30)(31)(32)(33)(34) have been employed. The detection efficiency of scintillators and storage-type phosphors depends on the volume of the material; thus, transparent materials are preferable to detect emissions generated inside materials.…”
Section: Introductionmentioning
confidence: 99%